PENERAPAN MATEMATIKA PADA EKONOMI DAN BISNIS : FUNGSI LINIER PADA SUBSIDI DAN PAJAK - Aldi Saouma Muhiban; Bunga Citra Lestari; Ferlin Adinda Nirtadiansyah; Gek Geya Rahma; Muhammad Nashirudin; Nabila Putri Adriyani (CV. Denasya Smart Publisher, 2025)
Taxes and subsidies are two important instruments in economic policy that are often used by governments to achieve various macroeconomic goals. Taxes are mandatory contributions imposed on individuals or business entities to finance government expenditure, while subsidies are assistance or incentives provided by the government to reduce the cost burden on certain goods or services. Taxes play a role in funding the state budget which is used to provide various public services, such as infrastructure, education and health. Meanwhile, subsidies are often provided to keep the prices of important goods or services affordable for the public, especially in strategic sectors such as energy, food and transportation. These two policies, although they have different goals, are often interrelated in an effort to create economic and social stability. However, both taxes and subsidies have challenges and impacts that need to be considered. High taxes can burden society, while untargeted subsidies can cause market distortion and dependency. Therefore, careful planning and regular policy evaluation are essential to ensure the sustainability and effectiveness of these policies in promoting inclusive and equitable economic growth.